Reconstruction of the proto-type basin and tectono-paleographical evolution of Tarim in the Cenozoic - Wei, Lunyan; Huang, Shaoying; Luo, Caiming; Duan, Yunjiang; Xia, Jinkai; Zhong, Ziqi; Li, Xiang; Chang, Haining (Frontiers in Earth Science, 2023)
The Tarim Basin is the largest sedimentary basin in China, and it has experienced a complex tectonic evolutionary history. Reconstruction of the proto-type basin and tectono-paleogeography is helpful to understand the different stages of evolution of the sedimentary basin and basin-mountain relationship. It is significant to combine the basin with the regional tectonic background to discuss the process of basin-mountain coupling and the tectonic evolution of the peripheral orogenic belts. With a reliable residual thickness map and lithofacies map of the Tarim Basin in the Cenozoic, based on the amount of shortening we quantified from previous works and 81 balanced cross-sections, we restored the original range and compiled the proto-type basin map of Tarim Basin. From a compilation of previous studies on the lithofacies of peripheral blocks, the tectono-paleogeography of the Tarim Basin in Cenozoic has been reconstructed. The Indian Plate collided with the Eurasian continent at ∼45–40 Ma. The remote effect of the collision led to the resurrection and reactivation of the Kunlun and Tianshan Mountains. The Southwest Tarim and Kuqa rejuvenated foreland basins separately developed along the north front of the Kunlun Mountains and the south front of the Tianshan Mountains. The tectonic evolution process of the Tarim Basin in the Cenozoic was divided into two stages: 1) in the Paleogene, the Neo-Tethys Ocean retreated stepwise westward from the Southwest of the Tarim Basin, and the sedimentary lithofacies of the Southwest Tarim Depression were bay lagoon facies and lake facies; 2) the Neo-Tethys Ocean retreat finally occurred in the Tarim Basin during the Late Oligocene to Early Miocene, and it became an almost closed terrestrial basin, with the deposition of fluvial facies and lacustrine facies. The Cenozoic tectono-paleogeography of the Tarim Basin is closely related to the closure of the Neo-Tethys Ocean and the reactivation of the Kunlun and Tianshan Mountains.